Пам’ятки середньодніпровської культури Середнього Подесення - Куриленко, В.Є.; Бунятян, К.П. (Археологія, 2006)
У статті подано опис нових пам’яток середньодніпровської культури. На картах памятников среднеднепровской культуры (СДК) территория Среднего Подесенья представлена белым пятном. Между тем наблюдения В.Е. Куриленко только в одном небольшом регионе существенно меняют эту ситуацию.
На Черниговщине на отрезке Десны от юга Новгород-Северского р-на до впадения в нее р. Сейм (преимущественно
Коропский р-н) выявлено густую сеть памятников — около 40 местонахождений керамики СДК. Отражают они,
видимо, поселения, главным образом, типа стойбищ, хотя не исключены и более долговременные. Выявлены здесь
и отдельные грунтовые погребения, которые явно входили в состав небольших могильников.
Хронологически дифференцировать материал сложно, поскольку речь идет о сборах, зачистках и небольших
шурфах. В целом эти памятники представляются синхронными поселениям Среднего Поднепровья и отражают
поздний этап развития СДК. The territory of the Middle Desna River region is a blank spot on the maps of the monuments of the Middle Dnipro River
culture (MDC) (see, for example: Artemenko 1987, Map 3). In the meantime, V.Ye. K urylenko’s observations for only one
small area fundamentally change the situation. The Chernihiv Region was revealed to have a dense network of monuments
– about 40 occurrences of MDC ceramics at the section of Desna River from the south of Novhorod-Siverskyj Region to
the place where it meets Seim River (mostly Korop Region). They mainly seem to represent settlements of the station type,
although more long-term ones are quite possible. Also individual burials without mounds, which were obviously a part of
small burial grounds were discovered here.
It is difficult to differentiate this material chronologically, since we only deal with pick up material, occasional
cleaning and small prospecting shafts. In general these monuments seem to be synchronous to the settlements of the
Middle Dnipro River region (Bondar 1974) and reflect the later stage of development of MDC.